Konsep Privacy Menurut Orang Jawa, Sebagaimana Terlihat dari Tata Ruang Rumah Tradisional Jawa - Ary Wahyono (Jurnal Masyarakat dan Budaya, 1998)
This writer examines the relationship between privacy and space system in the traditional houses of Javanese. This concept as reflected by building of houses is much related with their world view or cosmology.